2022
DOI: 10.1155/2022/2177991
|View full text |Cite
|
Sign up to set email alerts
|

Shrunken Pore Syndrome Is Associated with Renal Function Decline in Female Patients with Kidney Diseases

Abstract: Background. Shrunken pore syndrome (SPS) represents selective impairment of kidney filtration of low-molecular-weight molecules between 1 and 30 kDa and has been related to outcomes including morbidity, mortality, and cardiovascular events. However, the prevalence and kidney outcomes of SPS have not been investigated in patients with IgA nephropathy (IgAN) and membranous nephropathy (MN). Methods. We retrospectively collected information of 536 patients including 414 with IgAN and 122 with MN. SPS was mainly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In patients with IgA nephropathy and membranous nephropathy, women were not overrepresented in patients with SPS. However, there was a significant association between SPS and end-stage renal disease in females, but not in males [ 38 ]. In healthy volunteers aged 60 years or older, the eGFR CYSTATIN /eGFR CKD-EPI ratio was significantly higher in women and increased progressively with age in both genders [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IgA nephropathy and membranous nephropathy, women were not overrepresented in patients with SPS. However, there was a significant association between SPS and end-stage renal disease in females, but not in males [ 38 ]. In healthy volunteers aged 60 years or older, the eGFR CYSTATIN /eGFR CKD-EPI ratio was significantly higher in women and increased progressively with age in both genders [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a significantly lower eGFRcys than eGFRcr may also be a manifestation of kidney disease, [27][28][29] which is mainly manifested in glomerular filtration dysfunction of medium-sized molecules, 27,30 such as cystatin C. And, eGFRdiff is negatively correlated with the severity of this novel kidney disease. 31 Moreover, this disease may cause the decline of the resistance and defense of the kidneys 32 and lead to a tendency of CA-AKI when hit by the contrast agent. Besides, patients with either CKDcys or CKDcr were found to be associated with CA-AKI development in this study.…”
mentioning
confidence: 99%